1995
DOI: 10.1007/bf00311459
|View full text |Cite
|
Sign up to set email alerts
|

The liver regenerative response elicited by antisecretory agents in partially hepatectomized rats: A comparison between omeprazole and famotidine

Abstract: Liver regeneration after omeprazole (OMP) or famotidine (FAM) administration was examined in 66% hepatectomized rats. The regeneration was evaluated by the liver weight as a percentage of body weight (LRR) and the proportion of hepatocytes in mitosis per 1,000 counts (MI). Administration of OMP 0.4 mg/kg per day for 3 or 7 days suppressed LRR and MI 3 and 7 days after hepatectomy. However, the administration of FAM 0.8 mg/kg per day for 3 or 7 days did not change either LRR or MI. Increased gastrin levels in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2003
2003
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
3
0
3
Order By: Relevance
“…Ambas são inibidoras da bomba de prótons (H+, K+-ATPase) e atuam na redução da secreção gástrica 4 . Por isso, são bastante usadas profilaticamente no período pós-operatório de ressecções hepáticas para aliviar o stress cirúrgico e evitar a formação de úlceras e, conseqüentemente, sangramento 5 . , o omeprazol, aplicado durante 3 dias após a hepatectomia, estimulou a regeneração hepáti-ca com 0,2 mg/Kg ao dia e a inibiu com 0,4 mg/Kg ao dia.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Ambas são inibidoras da bomba de prótons (H+, K+-ATPase) e atuam na redução da secreção gástrica 4 . Por isso, são bastante usadas profilaticamente no período pós-operatório de ressecções hepáticas para aliviar o stress cirúrgico e evitar a formação de úlceras e, conseqüentemente, sangramento 5 . , o omeprazol, aplicado durante 3 dias após a hepatectomia, estimulou a regeneração hepáti-ca com 0,2 mg/Kg ao dia e a inibiu com 0,4 mg/Kg ao dia.…”
Section: Resultsunclassified
“…Várias drogas, entre elas omeprazol e pantoprazol, são usadas para tratar essas úlceras e, profilaticamente, para evitar sua formação 3,4 . Alguns estudos mostraram que o omeprazol, a depender da concentração, tanto pode inibir quanto estimular a regeneração do fígado 5,6 . Quanto ao efeito do pantoprazol, nenhum estudo foi encontrado.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…One study reports negative effects [20] , whereas the lack of any effect [23] and positive effects [24] have been reported in others. De Melo et al [20] also reported in their experimental study that pantoprazole has no effect on liver regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Aono [23] reported that omeprazole constrains liver regeneration and increases the level of transaminases in 66% of hepatectomy models performed on rats. In contrast, Ohtake et al [24] reported that following partial hepatectomy of rats, liver regeneration was stimulated, the cytotoxic effect of omeprazole was not observed, and the mitotic index of omeprozole-treated rats on the 3rd day was significantly increased compared to the control group.…”
Section: Discussionmentioning
confidence: 99%